Análisis de la información en canales informativos del estado y la posverdad en tiempos de covid-19 - Rojas Encalada, Lady Daniela (2020)
The present research work was based on the analysis of the information in the state and post-truth news channels in times of covid, with the aim of carrying out a content analysis of the national channels that were broadcast during the month of March with respect to to the current health emergency, in order to establish a category of messages that were transmitted to the population. The development of theoretical support is supported by bibliographic sources on this subject of study. The techniques that were used were the observation of the audiovisual material of the national chains compiled from pages and web platforms, the bibliographic investigation, the interview with a journalist from the city, Mr. Marlon Goya Mallea, which allowed to know first-hand information about the topic of interest and the survey carried out with citizens to analyze their points of view and contrast the information. Throughout this case analysis, the importance of good government communication with citizens is exposed, since in this way it will only be possible to generate an agreement, because if there is no general approval of the principles, a successful administration cannot be made. This is why, at present, the way in which the national channels presented, the information that was released, the facts that were hidden, among others, caused a lot of mistrust and uncertainty in every country.